Tourniquet use for extremity fractures has no adverse effect on number of ventilator days for patients who are treated with reamed femoral or tibial shaft nails. Issue 11 (November 2020) - Coale, Max; Costales, Timothy; Zerhusen, Timothy; Baker, Mitchell; Pollak, Andrew N.; Jarman, Molly P.; Castillo, Renan C.; O'Toole, Robert V.
Highlights: No statistically significant negative association was found between use of a tourniquet and number of ventilator days in the femoral or tibial fracture group. Tourniquet use for other fractures did not increase the number of ventilator days for patients undergoing intramedullary nail insertion to treat femoral or tibial shaft fractures. A potential protective effect of tourniquet use was shown in patients with upper extremity fractures and in those with both upper and lower extremity fractures. The data presented in this study should reassure clinicians that tourniquet use for other fractures in either the upper or lower extremity at the same setting as reamed femoral or tibial nail insertion does not seem to increase risk for increased ventilator-dependent days. Abstract: Introduction: Concern exists regarding the pulmonary effects of using tourniquets for secondary extremity fractures in patients also undergoing intramedullary nail (IMN) fixation of femoral or tibial shaft fractures. Our hypothesis was that tourniquet use would be associated with increased ventilator days. Methods: At a Level I trauma center, we conducted a retrospective review of 1966 patients with 2018 fractures (1070 femoral shaft and 948 tibial shaft) treated with IMN from December 2006 to September 2014. Medical record review and bivariate and multiple variable regression analyses were conducted, and the main outcome measurement was number of ventilator days. Results: No statistically significant negative association was found between use of a tourniquet and number of ventilator days in the femoral or tibial fracture group. Use of tourniquets in the upper extremities showed a statistically significant decrease in amount of ventilator days in the femoral group (−2.2 days, p = 0.003) but no association in the tibial group (1.1 days, p = 0.36). Use of tourniquets concurrently in both upper and lower extremities of both femoral and tibial groups also had a protective effect (−6.8 days, p < 0.001 and −2.3 days, p = 0.009, respectively). Stratified and sensitivity analyses (to account for effects of mortality and missing data) showed consistently similar results. Conclusion: Tourniquet use for secondary extremity fractures, in patients also undergoing IMN fixation for femoral or tibial shaft fractures, was not associated with an increased number of ventilator days. A potential protective effect of tourniquet use was shown in patients with upper extremity fractures and in those with both upper and lower extremity fractures. Level of evidence: Therapeutic Level III (Retrospective cohort study).